Review of The Effectiveness of Oral B12 Supplementation with Oral Mecobalamin In Diabetic Neuropathy Patients - Laxmita Permata Winardi (Green Publisher Indonesia, 2026)
Diabetic neuropathy is a common complication of diabetes mellitus that significantly affects patients' quality of life. Vitamin B12 supplementation has emerged as a potential therapeutic approach, yet the effectiveness of oral vitamin B12 (cyanocobalamin) compared to its active form (mecobalamin) remains debated. This study aims to evaluate and compare the effectiveness of oral vitamin B12 and oral mecobalamin supplementation in managing diabetic neuropathy. A systematic literature review approach was employed, analyzing studies published between 2017 and 2025. Data were sourced from PubMed, Google Scholar, ScienceDirect, and Cochrane using specific keywords. Articles were selected based on predetermined inclusion and exclusion criteria, focusing on clinical trials, systematic reviews, and meta-analyses comparing cyanocobalamin and mecobalamin. Qualitative content analysis was conducted, emphasizing clinical outcomes, symptom scores, B12 levels, and nerve conduction parameters. Findings reveal that mecobalamin is more effective than cyanocobalamin in reducing neuropathic symptoms. Long-term metformin use is significantly associated with decreased vitamin B12 levels, increasing the risk of peripheral neuropathy. Mecobalamin shows greater clinical effectiveness in the management of diabetic neuropathy than standard oral vitamin B12. Routine B12 level monitoring is highly recommended in diabetic patients on metformin therapy to prevent neurological complications.